Synthesis of ZnO Nanoparticles by Co-Precipitation Method: Effect of Washing on the Purity of the Nanoparticles - Mim, Samiya Rahman; Monda, Sudipta; Jamal, Moniruzzaman; Billah, Md Muktadir (Chemical Engineering Research Bulletin, 2023)
The objective of this study was to investigate the influence of washing on purity of the synthesized ZnO nanoparticles (NPs). Here, co-precipitation method was followed to synthesize ZnO NPs, which involved washing and annealing of Zn(OH)2 precipitates in facilitating the conversion into ZnO. XRD analysis indicated the formation of hexagonal wurtzite crystal structure of ZnO. However, an unwanted peak at 29.4° was observed, which prompted further deeper analysis. Rietveld analysis performed to identify the root cause revealed that the presence of nitrate salt, which was formed during the precipitation reaction between Zn(NO3)2.6H2O and NaO3, was accountable for the extra peak. Inadequate washing was suspected to be the reason and subsequent thorough washing resulted in disappearance of the extra peak and the emergence of single phase ZnO NPs. These results highlight the importance of thorough washing when using the co-precipitation approach to obtain pure ZnO nanoparticles free of any undesirable contaminants. The effect of increasing annealing temperature was also found to be effective to resolve this issue with limitation of crystallite size control. Chemical Engineering Research Bulletin 23(2023): 26-29